Phytochemical profile of commercially available food plant powders: their potential role in healthier food reformulations. (15th July 2015) - Neacsu, M.; Vaughan, N.; Raikos, V.; Multari, S.; Duncan, G.J.; Duthie, G.G.; Russell, W.R.
Highlights: Food plant powders' phytochemical content was measured by targeted LC–MS/MS analysis. Total phytochemical content in mg kg −1 was around 130 in green pea to 930 in spinach. Food plants phytochemical content represents valuable information for the industry. Food industry could exploit this information on re/-formulation of healthier foods. Abstract: Reformulation of existing processed food or formulation of new foods using natural products (plant-based) will inherently confer to new products with less calories, fat, salt, phosphates and other synthetic components, and higher amounts of fibre, antioxidants, vitamins and other beneficial components. Plant ingredients, such as food plant powders, are currently being used in food manufacturing, predominantly for flavouring and colouring purposes. To expand their use as a food ingredient, freeze-dried powders representing major vegetable groups were characterised by targeted LC–MS/MS analysis of their phytochemicals. All the plant powders were found to be rich in flavonoids, phenolic acids and derivatives; total content in these compounds varied from around 130 mg kg −1 (green pea) to around 930 mg kg −1 (spinach). The food plant powders' phytochemical content represents valuable information for the food industry in the development of healthier novel foods and for the reformulation of existing food products in relation to antioxidants, food preservatives and alternatives to nitrite use.